2021
DOI: 10.5194/acp-21-5439-2021
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of ice-nucleating particle concentrations affects the radiative properties of tropical convective cloud systems

Abstract: Abstract. Convective cloud systems in the maritime tropics play a critical role in global climate, but accurately representing aerosol interactions within these clouds persists as a major challenge for weather and climate modelling. We quantify the effect of ice-nucleating particles (INPs) on the radiative properties of a complex tropical Atlantic deep convective cloud field using a regional model with an advanced double-moment microphysics scheme. Our results show that the domain-mean daylight outgoing radiat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 86 publications
(161 reference statements)
0
66
0
Order By: Relevance
“…This assumes that each ice nucleation site has a characteristic temperature at which it always becomes active and time dependence is insignificant (Herbert et al, 2014), otherwise known as the singular description of heterogeneous ice nucleation (Koop and Zobrist, 2009;Murray et al, 2012;Vali, 1994;Pruppacher, 1978). Characterising icenucleating materials in terms of ns(T) also forms the basis of models used for predicting the temperatures (and thus cloud regime) at which different classes of atmospheric INPs may become active (Vergara-Temprado et al, 2017;Hawker et al, 2021;Zhao et al, 2021;Murray et al, 2012).…”
Section: Ice Nucleation Measurements By Droplet Freezing Assay and Determination Of Samples' Heat Deactivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumes that each ice nucleation site has a characteristic temperature at which it always becomes active and time dependence is insignificant (Herbert et al, 2014), otherwise known as the singular description of heterogeneous ice nucleation (Koop and Zobrist, 2009;Murray et al, 2012;Vali, 1994;Pruppacher, 1978). Characterising icenucleating materials in terms of ns(T) also forms the basis of models used for predicting the temperatures (and thus cloud regime) at which different classes of atmospheric INPs may become active (Vergara-Temprado et al, 2017;Hawker et al, 2021;Zhao et al, 2021;Murray et al, 2012).…”
Section: Ice Nucleation Measurements By Droplet Freezing Assay and Determination Of Samples' Heat Deactivationsmentioning
confidence: 99%
“…INPs are important because newly formed ice crystals can grow at the expense of supercooled liquid droplets. This is a process that strongly modulates the radiative properties of shallow mixed-phase clouds (i.e., their albedo) (Storelvmo and Tan, 2015;Murray et al, 2021), can initiate precipitation by enhancing collision and coalescence processes (Vergara-Temprado et al, 2018;Rosenfeld et al, 2011) and can influence anvil cirrus properties in deep convective systems (Hawker et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This study introduces the methodological framework to study the sensitivity of a climate model to the representation of CMP processes. To complete it, the analysis needs to be expanded to include other CMP processes in the model: For cold CMP ice formation, regional modeling studies have demonstrated cloud susceptibility to the choice of the ice nucleation parameterisation (Levkov et al, 1995;Hawker et al, 2021b), whereas in ECHAM-HAM heterogeneous immersion freezing in mixed-phase clouds has been shown to be rather inefficient (Villanueva et al, 2021). More generally the heterogeneous ice formation pathway in mixed-phase clouds is small in ECHAM-HAM (Dietlicher et al, 2019;Bacer et al, 2021), hinting at simplification potential.…”
Section: Processmentioning
confidence: 99%
“…In a sensitivity study of CMP parameters, found that the time scale of the Wegener-Bergeron-Findeisen process explains a large variance in supercooled cloud fractions, suggesting that as a whole it may be a dominating process as well. Secondary ice formation (Korolev and Leisner, 2020) may interact with the ice crystal source processes, allowing for interactive sensitivities (Hawker et al, 2021b), and should therefore be included, even though only the Hallet-Mossop process is optionally included in ECHAM-HAM (Neubauer et al, 2019). Moreover, for a complete CMP process investigation, of course the warm rain processes need to be included as well (Wood et al, 2009;Gettelman et al, 2013)).…”
Section: Processmentioning
confidence: 99%
“…This determines the concentration of INP at lower mixed-phase altitudes and therefore the altitude of liquid depletion due to heterogeneous freezing in the lower and middle mixed-phase cloud levels (e.g. Hawker et al, 2021;Takeishi and Storelvmo, 2018).…”
Section: Introductionmentioning
confidence: 99%